In vitro activity and time‐kill curve analysis of sitafloxacin against a global panel of antimicrobial‐resistant and multidrug‐resistant Neisseria gonorrhoeae isolates. Issue 1 (20th November 2017) - Jönsson, Agnez; Foerster, Sunniva; Golparian, Daniel; Hamasuna, Ryoichi; Jacobsson, Susanne; Lindberg, Magnus; Jensen, Jörgen Skov; Ohnishi, Makoto; Unemo, Magnus
Abstract : Treatment of gonorrhoea is a challenge worldwide because of emergence of resistance in N . gonorrhoeae to all therapeutic antimicrobials available and novel antimicrobials are imperative. The newer‐generation fluoroquinolone sitafloxacin, mostly used for respiratory tract infections in Japan, can have a high in vitro activity against gonococci. However, only a limited number of recent antimicrobial‐resistant isolates from Japan have been examined. We investigated the sitafloxacin activity against a global gonococcal panel (250 isolates cultured in 1991–2013), including multidrug‐resistant geographically, temporally and genetically diverse isolates, and performed time‐kill curve analysis for sitafloxacin. The susceptibility to sitafloxacin (agar dilution) and seven additional therapeutic antimicrobials (Etest) was determined. Sitafloxacin was rapidly bactericidal, and the MIC range, MIC50 and MIC90 was ≤0.001–1, 0.125 and 0.25 mg/L, respectively. There was a high correlation between the MICs of sitafloxacin and ciprofloxacin; however, the MIC50 and MIC90 of sitafloxacin were 6‐fold and >6‐fold lower, respectively. Sitafloxacin might be an option for particularly dual antimicrobial therapy of gonorrhoea and for cases with ceftriaxone resistance or allergy. However, further in vitro and particularly in vivo evaluations of potential resistance, pharmacokinetics/pharmacodynamics and ideal dosing for gonorrhoea, as well as performance of randomized controlled clinical, trials are crucial.